The Taylor–Quinney coefficients and strain hardening of commercially pure titanium, iron, copper, and tin in high rate compression. (October 2021) - Soares, G.C.; Hokka, M.
Highlights: β int and β diff of four metals were measured with a high speed IR camera. Both β and strain hardening parameters describe microstructural evolution. β int increased from a lower value (0.2–0.7) to a higher saturation value (0.8–0.95). The observed β diff >1 implies a higher rate of heat generation than that of applied plastic work. Abstract: This work presents an investigation on the effects of adiabatic heating and strain rate on the dynamic compressive response of titanium, iron, copper, and tin. The high strain rate tests were carried out with a Split Hopkinson Pressure Bar (SHPB) and the low strain rate tests with a servohydraulic testing machine. The temperature increase of the specimens during deformation was measured with high speed infrared thermography (IRT). The results show that all the investigated materials have positive strain rate sensitivity and temperature increases of up to 65 °C were observed in the high strain rate experiments (500–3100 s −1 ). Adiabatic heating in all investigated materials increased with strain rate. The temperature increase at the strain rate of 1 s −1 clearly diminished the strain hardening rate of iron and titanium but was seemingly insufficient to impact the mechanical behavior of copper and tin. The Taylor–Quinney coefficients ( β int and β diff ) were found to be strain and strain rate dependent. At higher strain rates (1200–3100 s −1 ), the integral β int was smaller in the beginning of the test (0.2 to 0.7) and increased to approximately 0.8–0.9 at larger plastic strains. The differential β diff comprised gaussian curves as a function of strain whose maximum values were from 0.9 to 1.2 for the investigated materials. Tin had lower β int and β diff with higher strain hardening rates, while copper had a higher β int and β diff with a low strain hardening rate throughout the high strain rate tests. These results indicate that copper had a more stable microstructure during deformation and converted most of the applied plastic work into heat, while tin had a faster evolving microstructure which stored more plastic work in its microstructure during plastic deformation. Furthermore, this suggests that β int and β diff can be used as parameters to investigate the stability and the microstructural evolution of materials under high strain rate plastic deformation. β diff is more appropriate to describe the instantaneous thermomechanical behavior of a material and β int is more appropriate for applications which benefit from a single parameter to characterize how efficiently a material converts plastic work into heat up to a given strain level.